THE CONSTITUION OF GENDER DISSERTATION-ARGUMENTATIVE: ANALYSIS OF WORDING OF THE PROPOSED STATEMENT ABOUT INTERNET ENEM AND FUVEST - Soares, Nathalia Maria [UNESP] (Univ Estado Rio Grande Norte, 2015)
The objective of this research is to understand the statements of proposal writing applied in entrance examinations (ENEM and FUVEST), a literature search was conducted the theoretical and methodological framework of Bakhtinian discourse studies, mobilizing concepts like: gender; statement; ideological statement of values; subject; otherness and exotopy. we used the concept of dissertation by Granatic, and he proposed dissertation and argumentative ENEM 2011 and FUVEST 2008. These proposals were chosen for working with the same theme internet, but with elaborate set out in different ways. The analysis of the statements reveals that the statements of proposed texts productions aren't identical, which creates new meanings, new finishes around each statements and even new genres of speech. Fact which shows that the statement is relatively stable, it is a variety of genres, one of them is gender-argumentative, causing the subjects writers and evaluators transpose your thoughts by otherness and exotopy, building new statements.
Keywords: Statement; studies Bakhtinianos; proposal writing